Subjectivity Bias Elimination in Employee Appraisal Process – Role of People Analytics - Saha , Debadrito (Gyan Management Journal, 2022)
Purpose: This research serves the purpose of dealing with different types  of Human Subjective Biases in Performance Management System by  interview-based analysis and content analysis depending upon inputs from  renowned HR professionals and then to determine if HR Analytics can help  the HR practitioners in objective-decision making rather than intuition in PMS.Design/Methodology/Approach: Focused-Group-Interview approach  is followed here to acquire in-depth information about Subjectivity Bias  Elimination in Employee Appraisal Process and how the same can be  mitigated with the help of People Analytics.  Findings: This research will reveal the truth of erroneous subjective  judgments based on instincts and how HR Analytics can help the HR  practitioners in objective decision making rather than intuition in PMS. Originality/ Value: This research identifies factors leading to Subjectivity  Bias in Employee Appraisal Process. It suggests updated criteria for HR  professionals to mitigate subjectivity bias in Employee Appraisal Process  with help of People Analytics.
Keywords: Human Resource Analytics; Appraisal Process; Performance Management; Human Subjective Bias; Objective Decision Making